A Case of Conjunctival Melanoma Presenting as a Squamous Cell Carcinoma - Feliciana Menna; Markus Tschopp; Peter Meyer; Anthia Papazoglou (Case Reports in Ophthalmology)
Introduction: Conjunctival melanoma (CM) is a rare but potentially lethal ocular malignancy that arises from melanocytes in the conjunctiva. Its clinical presentation can mimic other more common conjunctival lesions, such as squamous cell carcinoma (SCC), leading to diagnostic challenges. Case Presentation: We present a case of CM initially misdiagnosed as conjunctival SCC due to overlapping clinical features. Conclusion: CM presenting as nonpigmented, conjunctival tumor is a diagnostic challenge. Clinicians should maintain a high index of suspicion for conjunctival melanocytic or amelanotic lesions, particularly those with atypical features.